Relationship between Farmers’ Characteristics and Organic Farming System Implementation of Paddy Rice with Farmers' Income - Aisyah, Siti; Faqih, Achmad; Suharni, Suharni; Sunani, Sunani; Lesmana, Indra; Rochman, Abdul (Devotion : Journal of Research and Community Service, 2023)
Agriculture is an important sector in the national economy, therefore the development priority is placed on development in the economic sector with an emphasis on the agricultural sector. Income in farming activities generally cannot be stable from time to time. The objectives of this study include (1) to determine the relationship between farmer characteristics and farmer income in farmer groups BPP Plumbon District, (2) to determine the relationship between the implementation of organic rice farming systems and farmer income in farmer groups BPP Plumbon District, (3) To determine the relationship between the characteristics of farmers and the implementation of organic rice farming systems with farmers' income in the BPP Farmer Group, Plumbon District. The research design used in this study was a quantitative research with a descriptive survey research technique. The results showed that: (1) there was a moderate relationship between farmer characteristics and farmer income in the BPP Farmer Group in Plumbon District, namely 0,703, (2) there is a moderate relationship between the application of organic rice farming systems and farmers' income in the BPP Farmer Group in Plumbon District, namely 0.643, (3) there is a significant relationship between farmer characteristics and the application of organic farming systems to farmer incomes. Based on the output that tarithmetic X1 = 7.551 and X2 = 5.252> ttable which is 1.998.